Correlation Between The Parenting Pattern with Confidence In Children Preschool (3-5 years) in TK IV Saraswati Denpasar 2012. - Ayu Puspita S, Ni Made (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
Early childhood (preschool) is a golden age for child's development. During the preschool, children learn to become more independent, and children must have confidence to become more independent. Based on an early survey result which is done at  TK Saraswati IV Denpasar, has got 25% of children have less confidence. Parenting patterns for educating children were important for shaping some of the basic attitude that will determine the development of the child's self confidence in the future. This research aims to determine the correlation of parenting parents with confidence in preschool children (3-5 years). This study using Descriptive Correlational method with Cross Sectional approach. Sample consisted of 55 preschool children (3-5 years) in group A TK IV Saraswati and taken by using a total sampling technique. The data was collected by answer the questionnaire. The results showed that most parents with good parenting (democratic) have children with high confidence that 17 people (50%), whereas parents with more authoritarian parenting had a child with average confidence is that 5 people (45.5%), and parents with more permissive parenting had a child with low confidence that 5 people (50%). Based on the correlation test results of coefficient contingency, it was found that p value is 0.004 (p <0.05) which means that Ha is accepted, it means there is a significant correlation between parenting parents with confidence in preschool children (3-5 years). It is suggested to parents to better provide a more democratic parenting by continually to build self-confidence of children. Caregivers of children should give an education to the parents for implement democratic parenting.
Keywords: Parenting Pattern, Self Confidence, Children' s Preschool